2017
DOI: 10.1371/journal.pone.0175091
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected associated microalgal diversity in the lichen Ramalina farinacea is uncovered by pyrosequencing analyses

Abstract: The current literature reveals that the intrathalline coexistence of multiple microalgal taxa in lichens is more common than previously thought, and additional complexity is supported by the coexistence of bacteria and basidiomycete yeasts in lichen thalli. This replaces the old paradigm that lichen symbiosis occurs between a fungus and a single photobiont. The lichen Ramalina farinacea has proven to be a suitable model to study the multiplicity of microalgae in lichen thalli due to the constant coexistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
142
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(146 citation statements)
references
References 55 publications
(75 reference statements)
4
142
0
Order By: Relevance
“…Despite the 454pyrosequencing limitations described in Moya et al. (low‐coverage samples, the region selected, etc. ), this approach represents a powerful and complementary approach to traditional Sanger sequencing, and helped us to shed light on microalgal coexistence.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite the 454pyrosequencing limitations described in Moya et al. (low‐coverage samples, the region selected, etc. ), this approach represents a powerful and complementary approach to traditional Sanger sequencing, and helped us to shed light on microalgal coexistence.…”
Section: Discussionmentioning
confidence: 98%
“…Reads were processed as described in Moya et al. () and clustered based on S 99‐L 0.9 criteria. The consensus sequences of the OTUs were identified using the BLAST tool in the GenBank database (Altschul et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the rbcL marker generally shows lower resolution than the ITS rDNA, we did not further analyse it here. Although previously overlooked, the co‐occurrence of several phycobionts in individual lichen thalli (i.e., algal plurality) is a relative common phenomenon (Bačkor et al., ; Moya, Molins, Martinez‐Alberola, Muggia, & Barreno, ; Muggia, Baloch, Stabentheiner, Grube, & Wedin, ; Muggia et al., ; Onuț‐Brännström et al., ; Park et al., ; Voytsekhovich & Beck, ). We also obtained evidence for algal plurality in several Stereocaulon samples, which strengthens the potential of this lichen genus as a suitable model for high‐throughput sequencing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have previously reported this phenomenon (e.g. del Campo et al ., ; Dal Grande et al ., ; Moya et al ., ), lichen thalli are still predominantly considered as pair‐wise interactions between a lichen‐forming fungus and a single alga. Our results suggest that this view may oversimplify the complexity of lichen thalli.…”
Section: Discussionmentioning
confidence: 99%